Rationale and Design of the CONCERT-HF Trial (Combination of Mesenchymal and c-kit+ Cardiac Stem Cells As Regenerative Therapy for Heart Failure). Issue 12 (8th June 2018) - Bolli, Roberto; Hare, Joshua M.; March, Keith L.; Pepine, Carl J.; Willerson, James T.; Perin, Emerson C.; Yang, Phillip C.; Henry, Timothy D.; Traverse, Jay H.; Mitrani, Raul D.; Khan, Aisha; Hernandez-Schulman, Ivonne; et al.
Abstract : Rationale: : Autologous bone marrow mesenchymal stem cells (MSCs) and c-kit + cardiac progenitor cells (CPCs) are 2 promising cell types being evaluated for patients with heart failure (HF) secondary to ischemic cardiomyopathy. No information is available in humans about the relative efficacy of MSCs and CPCs and whether their combination is more efficacious than either cell type alone. Objective: : CONCERT-HF (Combination of Mesenchymal and c-kit + Cardiac Stem Cells As Regenerative Therapy for Heart Failure) is a phase II trial aimed at elucidating these issues by assessing the feasibility, safety, and efficacy of transendocardial administration of autologous MSCs and CPCs, alone and in combination, in patients with HF caused by chronic ischemic cardiomyopathy (coronary artery disease and old myocardial infarction). Methods and Results: : Using a randomized, double-blinded, placebo-controlled, multicenter, multitreatment, and adaptive design, CONCERT-HF examines whether administration of MSCs alone, CPCs alone, or MSCs+CPCs in this population alleviates left ventricular remodeling and dysfunction, reduces scar size, improves quality of life, or augments functional capacity. The 4-arm design enables comparisons of MSCs alone with CPCs alone and with their combination. CONCERT-HF consists of 162 patients, 18 in a safety lead-in phase (stage 1) and 144 in the main trial (stage 2). Stage 1 is complete, and stage 2 is currently randomizing patients from 7 centers across the United States. Conclusions: : CONCERT-HF will provide important insights into the potential therapeutic utility of MSCs and CPCs, given alone and in combination, for patients with HF secondary to ischemic cardiomyopathy. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT02501811.